Urbanization in Nigeria - Mabogunje, Akin L. (New York: Africana Pub. Corp., 1969)
This book provides a comparative examination of traditional and modern urbanization in Nigeria.
Includes bibliographical references.
lje 16/05/2018
Loans
Keywords: Urbanization; Nigeria